Early postural adjustments in gait initiation in post-stroke subjects - Bento, Daniela (2015)
The success of gait initiation dependes of the ability on the central nervous system (CNS) to anticipate the perturbation related to the voluntary action through of postural adjustments: early postural adjustments (EPAs) and the antecipatory postural adjustments (APAs).